2018
DOI: 10.18596/jotcsa.389075
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity and Biological Potential of Tanacetum praeteritum subsp. praeteritum Essential Oils

Abstract: Two samples of Tanacetum praeteritum (Horwood) Heywood subsp. praeteritum (Horwood) were collected in flowering period and subjected separately to hydrodistillation to yield the essential oils (A and B). The oils were investigated for chemical composition with GC-FID and GC/MS techniques and evaluated against acetylcholinesterase and -amylase enzymes and free radicals (DPPH • and ABTS •+ ) using microtiter plate assays. Both oils were characterized with high abundance of oxygenated monoterpenes. The oils were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…In this sense, Özek (2018) evaluated the in vitro α-amylase inhibitory effects of T. praeteritum ssp. praeteritum aerial parts essential oils using the Caraway Somogyi iodine/potassium iodide (IKI) method and acarbose as the reference drug.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Özek (2018) evaluated the in vitro α-amylase inhibitory effects of T. praeteritum ssp. praeteritum aerial parts essential oils using the Caraway Somogyi iodine/potassium iodide (IKI) method and acarbose as the reference drug.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The author indicated that the essential oil displayed α-amylase inhibitory features with an IC 50 value of 0.89 ± 0.13 mg/mL compared to acarbose 0.08 mg/mL. The author attributed the inhibitory effects to the high amount of oxygenated monoterpenes in the EO ( Özek, 2018 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Moreover, as initially disclosed, α-glucosidase inhibition effect was measured [21]. Additionally, the α-amylase inhibition experiment was subjected by adapting the procedure used by Caraway-Somogi iodine/potassium iodide method [22].…”
Section: Enzyme Inhibition Potentialsmentioning
confidence: 99%
“…These mice have a mutation in their leptin receptor, with the subsequent development of insulin resistance and obesity which was partially corrected by the administration of lemon balm essential oil ( Chung et al, 2010 ). Five experimental models used in vitro techniques for evaluating the effect of essential oils on important enzymes from glucose metabolism like α-amylase or α-glucosidase which are involved in the release of glucydic fractions in the digestive system ( Özek, 2018 ). In these models, the administration of essential oils inhibited the two enzymes with IC50 ranging from 0.5 to 8.16 µg/ml.…”
Section: Essential Oil-bearing Plants From the Balkansmentioning
confidence: 99%
“…Also, the inhibition of α-glucosidase was demonstrated by another in vitro study investigating the essential oil from Laurus nobilis L., which showed a 90% inhibition of the enzyme (IC50 of 1.748 µg/ml), the main chemical constituent responsible for the effect being 1,8-cineole ( Sahin Basak and Candan, 2013 ). The research of Özek (2018) identified a significant inhibition of α-amylase for the essential oil from Tanacetum praeteritum subsp . praeteritum (Horw.)…”
Section: Mechanisms Of Action Of Antidiabetic and Antihyperlipidemic mentioning
confidence: 99%